2016
DOI: 10.1038/ncomms13097
|View full text |Cite
|
Sign up to set email alerts
|

Purification of functional human ES and iPSC-derived midbrain dopaminergic progenitors using LRTM1

Abstract: Human induced pluripotent stem cells (iPSCs) can provide a promising source of midbrain dopaminergic (mDA) neurons for cell replacement therapy for Parkinson's disease (PD). However, iPSC-derived donor cells inevitably contain tumorigenic or inappropriate cells. To eliminate these unwanted cells, cell sorting using antibodies for specific markers such as CORIN or ALCAM has been developed, but neither marker is specific for ventral midbrain. Here we employ a double selection strategy for cells expressing both C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 42 publications
8
98
6
Order By: Relevance
“…Histological studies of mouse embryonic tissues were performed as previously described (Samata et al, 2016). Pregnant mice (C57BL/6NCrSlc) were obtained from Shimizu Laboratory Supplies (Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Histological studies of mouse embryonic tissues were performed as previously described (Samata et al, 2016). Pregnant mice (C57BL/6NCrSlc) were obtained from Shimizu Laboratory Supplies (Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…For amphetamine-induced rotational tests, data from six studies (16,17,20,21,23,25) were reported. One study (21) used two different iPSC lines, and had separate control group and outcomes.…”
Section: Efficacy Of Ipscsmentioning
confidence: 99%
“…For apomorphine-induced rotation tests, similarly, one study (24) was excluded from the pooled analysis due to the data being represented in the form of a ratio and one study (16) did not describe the outcome in detail; therefore, it was not possible to calculate the mean and SD. Thus only three experiments (21,25) were reported for evaluating the effect of iPSCs on apomorphine-induced rotation tests. The outcome used the fixed-effects model and indicated that iPSCs also improved the apomorphine-induced rotation tests (SMD, -1.45; 95% CI, -2.16 to -0.73; P<0.00001; heterogeneity: χ 2 =1.07, P=0.59, I 2 =0%; Fig.…”
Section: Efficacy Of Ipscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human‐induced pluripotent stem cells (hiPSCs) can provide a source for midbrain dopaminergic (mDA) neurons for cell therapy in Parkinson's disease. The pitfalls to this method are the remaining tumorigenic progenitors and contamination with mature cell types . Samata and colleagues introduce LRTM1—a novel cell‐surface marker expressed in the ventral midbrain (VM)—and provide evidence that by using anti‐LRTM1 antibodies, isolated mDA progenitors are able to differentiate into mature mDA neurons and produce eye‐catching clinical results.…”
mentioning
confidence: 99%